Hubungan Pengumuman Dividen Dengan Harga Saham Pada Industri Mining Dan Mining Service Di Bursa Efek Indonesia Tahun 2011 - Farah Margaretha; Rifqi Hadyan (Jurnal Manajemen dan Bisnis, 2012)
In determining the decision to conduct transactions in the capital market, investors will base their decisions on a variety of public information including dividend announcements relevant to the stock price. This study aimed to test whether there is a relationship between the dividend announcement stock price. Investors can not use the public announcement of the dividend as the relevant information if there is no relationship between the dividend announcement to acquire shares at a price of Abnormal Return. The sample in this study is the Mining and Mining Service Company listed on the Indonesian Stock Exchange announced a dividend in the year 2011 that as many as 28 companies were taken by using purposive sampling technique. Tests performed on twenty-one event study focused on three events, namely: 1) ten days before the announcement, 2) at the time of announcement, and 3) ten days after the announcement. To test the hypothesis used One Sample t - Test. The test results prove the hypothesis that there is no significant relationship between the dividend announcement stock price in the mining industry and mining services industry. This means that investors can not use the dividend announcement as a public information relevant to determine the stock price in the future. Ivestor also can not apply a strategy of active portfolio to get Abnormal Return, because there are many factors that could affect stock prices both internal and external factors.